Effect of membrane mechanics on AEM fuel cell performance. (16th November 2022) - Raut, Aniket; Fang, Haoyan; Lin, Yu-Chung; Sprouster, David; Yin, Yifan; Fang, Yiwei; Fu, Shi; Sharma, Sunil; Wang, Likun; Bae, Chulsung; Rafailovich, Miriam
Abstract : This work underscores the relationship between the mechanical properties of anion exchange membranes and pH, which together can have a profound effect on the power output of the fuel cells. Abstract : Anion exchange membranes (AEMs) are membranes with positively charged functional groups that enable anion transport. AEMs can be used as a solid ion conductor in hydrogen fuel cells, which have the potential for providing clean energy in an alkaline environment at low operating temperatures and with non-precious metals. AEMs are also used in water filtration, including in the process of desalination. As more applications of AEMs are explored, especially in non-ideal operational conditions, it is important to understand how their performance depends on the specific properties of their environment. For example, physical properties, such as shear modulus, Young's modulus, and storage modulus, can be correlated with an increased barrier to ion conduction and peak power output. This suggests that there is an optimum pH for performance because the alkaline solution interacts with the membranes to yield maximum flexibility that allows charges to flow through. In this study, meta -terphenyl fluoro-alkylene trimethylammonium ( m TPN1-TMA) membranes and Sustainion membranes were incorporated in a membrane electrode assembly (MEA) operated at different flow rates: (a) 600 sccm on the anode and 1200 sccm on the cathode (b) 700 sccm on the anode and 1400 sccm on the cathode. The pH of the solution inside the MEA was measured, and the membranes' relative surface modulus, Young's modulus, and storage modulus were measured by atomic force microscopy, Instron, and dynamic mechanical analysis, respectively. The modulus data suggest that the membrane stiffens at pH-9 and becomes more flexible at pH-10. Both m TPN1-TMA and sustainion membranes demonstrated higher power output at pH-10 suggesting that membrane flexibility is indeed necessary for ion conduction, without affecting durability. X-ray computed tomography (XCT) was performed on the cross-section of MEA to confirm the change in the thickness of the membrane owing to the different modulus at pH-9 and 10.